2000
DOI: 10.1177/01466216000241004
|View full text |Cite
|
Sign up to set email alerts
|

Latent and Manifest Monotonicity in Item Response Models

Abstract: The monotonicity of item response functions (IRF) is a central feature of most parametric and nonparametric item response models. Monotonicity allows items to be interpreted as measuring a trait, and it allows for a general theory of nonparametric inference for traits. This theory is based on monotone likelihood ratio and stochastic ordering properties. Thus, confirming the monotonicity assumption is essential to applications of nonparametric item response models. The results of two methods of evaluating monot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 42 publications
0
90
0
3
Order By: Relevance
“…A versão A do subteste de escrita obteve o valor de 0,68, sendo, portanto, satisfató-rio. A monotonicidade dos itens foi avaliada, e todos os itens obtiveram valores acima de 0,46, o que é tido como adequado para a utilização de modelos paramétricos da TRI (Junker & Sijtsma, 2000). Dessa forma, o conjunto de itens da versão A é satisfatório para a realização das análises via TRI.…”
Section: Análise De Dadosunclassified
“…A versão A do subteste de escrita obteve o valor de 0,68, sendo, portanto, satisfató-rio. A monotonicidade dos itens foi avaliada, e todos os itens obtiveram valores acima de 0,46, o que é tido como adequado para a utilização de modelos paramétricos da TRI (Junker & Sijtsma, 2000). Dessa forma, o conjunto de itens da versão A é satisfatório para a realização das análises via TRI.…”
Section: Análise De Dadosunclassified
“…So when we observe 0 rejections out of 1,000 replications Given the above results, it seems that CSN and MM are rather general properties of multivariate binary data. In fact, by reviewing the theory underlying monotonicity, Junker and Sijtsma (2000) showed that MM holds for the 1PLM. For the 2PLM these authors construct three theoretical counterexamples in which MM fails.…”
Section: First Experimentsmentioning
confidence: 99%
“…(16.14) Junker and Sijtsma (2000) showed that an MM result as in (] 6.14) is not obtained when R(_j) is rep]aced by X+. MM can be used to estimate the IRF by means of nonparametric regression.…”
Section: Mokken Sealing and Dimensionality Investigationmentioning
confidence: 99%
“…Second, P[Xj~xjIR(_j)l has been shown not to be monotone in general, thus losing MM (Junker & Sijtsma, 2000). Specifically, a nondecreasing observable curve, P[Xj~xjIR(_j)J, is neither a necessary nor a sufficient condition for Assumption M, but much practical experience with simulated data suggests that such monotone curves tend to be supportive of Assumption M. Software for estimating these curves is available (Molenaar & Sijtsma, 2000;Ramsay, 2000).…”
Section: Mokken Sealing and Dimensionality Investigationmentioning
confidence: 99%